2019
DOI: 10.1029/2018sw002132
|View full text |Cite
|
Sign up to set email alerts
|

The GIC and Geomagnetic Response Over Fennoscandia to the 7–8 September 2017 Geomagnetic Storm

Abstract: Between 7 and 8 September 2017, Earth experienced extreme space weather events. We have combined measurements made by the IMAGE magnetometer array, ionospheric equivalent currents, geomagnetically induced current (GIC) recordings in the Finnish natural gas pipeline, and multiple ground conductivity models to study the Fennoscandia ground effects. This unique analysis has revealed multiple interesting physical and technical insights. We show that although the 7–8 September event was significant by global indice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
128
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(139 citation statements)
references
References 46 publications
(101 reference statements)
10
128
0
1
Order By: Relevance
“…This is not obvious from the Dst and IE indices, but it is indicated by the peaks in ROTI and AATR. Strong electrodynamic processes are also evident considering the results of Dimmock et al (2019), who reported significant geomagnetically induced currents (GIC) at 18 UT in Fennoscandia. Since neither the solar wind and IMF, nor the geomagnetic indices show significant perturbations at that time, magnetosphereionosphere electrodynamics must be the source of the LSTID and the GIC.…”
Section: Dynamics Contributing To the Generation Of Lstidsmentioning
confidence: 82%
See 1 more Smart Citation
“…This is not obvious from the Dst and IE indices, but it is indicated by the peaks in ROTI and AATR. Strong electrodynamic processes are also evident considering the results of Dimmock et al (2019), who reported significant geomagnetically induced currents (GIC) at 18 UT in Fennoscandia. Since neither the solar wind and IMF, nor the geomagnetic indices show significant perturbations at that time, magnetosphereionosphere electrodynamics must be the source of the LSTID and the GIC.…”
Section: Dynamics Contributing To the Generation Of Lstidsmentioning
confidence: 82%
“…Thus, the IEC are horizontal equivalent ionospheric currents which correspond to the observed ground magnetic field. It is important to point out that, in reality, the true ionospheric currents correspond to a combination of horizontal and field-aligned currents, and it is not possible to distinguish those by using ground magnetometer data only (Pulkkinen et al, 2003;Dimmock et al, 2019). The IEC provide valuable information about the ionospheric electrodynamics and magnetosphere-ionosphere coupling and it is derived by the Finnish Meteorological Institute (FMI) using the spherical elementary current system method (Amm, 1997;Amm & Viljanen, 1999;Pulkkinen et al, 2003).…”
Section: Image Equivalent Currentsmentioning
confidence: 99%
“…Computations of the GEF within the second, most populated, group of papers (Beggan et al, ; Bailey et al, , ; Divett et al, ; Dimmock et al, ; Liu et al, ; Marshall et al, ; Nakamura et al, ; Püthe & Kuvshinov, ; Püthe et al, ; Pokhrel et al, ; Rosenqvist & Hall, ; Wang et al, , among others) rely on a numerical modeling of the GEF, either with a thin sheet or fully 3‐D conductivity models of the Earth. 3‐D conductivity models can be compiled using, for instance, results of regional MT surveys or/and exploiting global and regional maps of bathymetry, sediment thickness, etc.…”
Section: Introductionmentioning
confidence: 99%
“…These events can induce large geoelectric fields and geomagnetically-induced currents that can have harmful effects on electrical power grids. Nighttime perturbation events have often been associated with magnetic storms and auroral substorm onsets, but several studies have suggested that other, more localized magnetospheric and/or ionospheric processes, including poleward auroral expansions and small-scale ionospheric current vortices, also may drive these events [Viljanen, 1997;Pulkkinen et al, 2003;Huttunen et al, 2002;Ngwira et al, 2015Ngwira et al, , 2018Belakhovsky et al, 2018;Kozyreva et al, 2018, andDimmock et al, 2019].…”
Section: Introductionmentioning
confidence: 99%